VIDEO DOKUMENTER HERITAGE OF BUKITTINGGI PASAR SEKEN - ADIL ESTRAZA, Dr. Budiwirman, M.Pd., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The Pasar Seken of Bukittinggi city is a market area that sells various imported used clothing imported from various countries in the world. The clothes sold in the seken market have good quality at affordable prices. In its existence the seken market does not only become revenue turnover of the region but also becomes one of Bukittinggi's cultural heritageLack of understanding of the target audience and not optimal media in delivering information about the Bukittinggi Seken market is the main factor the author designed the Bukittinggi Secondary Documentary Video market. Documentary video media heritage of bukittinggi Pasa Seken is made in audio visual form so that the public can more easily understand information about the market as well as high. In addition to the documentary video, this information delivery was also supported by several other media that helped the main media to introduce the subject to the target audience, namely posters, stickers, t-shirts, pins, mugs, x-banners and wall clocks.The methodology used is the 5w + 1h approach, which is what, who, when (when), where (where), why (why) and how (how). By using the theory of 5w + 1h, all aspects summarized in the documentary videos of heritage of bukittinggi Pasa Seken can be packaged into audio visual media, heritage of Bukittinggi documentary videos Pasa Seken can be a media that has effective and communicative information for the target audience.keyword: Video Documenter, Pasar Seken, Bukittinggi.